PENGARUH PENGGUNAAN MODEL DISCOVERY TERHADAP HASIL BELAJAR TEMATIK DISEKOLAH DASAR - Porwasih, Regina; Kartono, Kartono; Margiati, K. Y. (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe problem in this research is how is the effect of discovery model toward student learning outcomes at thematic learning grade V Elemenatry School 03 Pontianak Selatan. This research aims to analyze the effect of discovery model on learning outcomes and analyze how much the influence of discovery model  toward thematic’s learning outcomes. This research used an experimental method with the Pre-Experimental Design of One Group Pretest-Posttest Design’s type. The population of grade V’s students SDN 03 Pontianak Selatan, the sampling was  purposive sampling type non-probability sampling that only uses grade VC. The technique used in data accumulation was the measurement with the data collecter instrument that used is an objective written test. Based on the data analysis, the average of students pre-test result  was 70.79 and the average of students post-test results was 77.32. After t test was obtained, t count was 7.11 while t table with dk = 34-1 = 33 and significant level (α) = 0.05% was 2.034. It turns out that t count ≥ t table or 7.11 ≥ 2.034 means that there is a significant effect on usage discovery model. From the results of the calculation of the effect size, obtained 0.78 with the medium category. This means that the use of discovery model has the influence on thematic’s learning outcomes on grade V SDN 03 Pontianak Selatan.  Keywords: Influence, discovery model, Learning Outcomes